Quality of cocoa (Theobroma cacao L.) DNA from foliar tissue at different stages of development (2018)
Theobroma cacao L. and its products are consumed worldwide. Those products are of great research interest due to antioxidant properties of some of their polyphenolic constituents. The amount of these polyphenols and polysaccharides has shown that can interfere with the high quality and quantity of nucleic acids for molecular research. Therefore, cocoa DNA extraction protocols can require a large amount of plant material and optimization time according with plant material source. The aim of this study was to evaluate the quality and quantity of DNA isolated from field plant leaves at different developmental stages from TSH565 genotype using different DNA extraction protocols. In addition, DNA extraction protocol was evaluated for small amount of young leaf tissue collected from in vitro plantlets from CCN51 and TSH565 genotype. Subsequently, the selectivity of different polymerase enzymes for PCR amplification using the obtained DNA was evaluated. This study revealed that D stage of development in field leaves was efficient for extraction of high-quality genomic DNA using the PowerPlant® Pro Kit modified (183.80 ng.µL-1 (1.98 A260/A280-1.98 A260/A230)). Highest DNA concentrations were obtained for FPL with 128.68 ng.µL-1 and 114.42 ng.µL-1 for CCN51 and TSH565 respectively and with IVL, which was obtained 54.24 ng.µL-1 for CCN51 and 56.52 ng.µL-1 for TSH565 per 0.1 g of leaf tissue. Taq DNA Polymerase recombinant of Thermo Scientific® showed the highest performance specifically for this study, contributing to the undoubted amplification of molecular markers like microsatellites (SSRs). The results obtained have allowed improvements in genetic analyses and molecular studies using a reduced amount of plant tissue.